2018
DOI: 10.1111/ans.14490
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic positive margins in papillary thyroid cancer do not impact disease recurrence

Abstract: Despite a strong association between microscopic positive margins and other adverse prognostic factors in PTC, there is no independent association with disease recurrence on multivariate analysis. Microscopic positive margins are rare (1.1%) in the absence of other indications for RAI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
(31 reference statements)
1
4
0
Order By: Relevance
“…They note significant differences in baseline characteristics between patients with clear margins and those with microscopic positive margins. 1 The strong association of positive margins with other adverse features is not unexpected and consistent with the literature. 2 We performed a multivariate analysis to elucidate the independent impact of microscopic positive margins whilst adjusting for these potential confounding factors and found no independent association with disease recurrence.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…They note significant differences in baseline characteristics between patients with clear margins and those with microscopic positive margins. 1 The strong association of positive margins with other adverse features is not unexpected and consistent with the literature. 2 We performed a multivariate analysis to elucidate the independent impact of microscopic positive margins whilst adjusting for these potential confounding factors and found no independent association with disease recurrence.…”
supporting
confidence: 86%
“…We read with interest the article by Abraham et al 1 Enrolling 610 patients undergoing surgery for papillary thyroid carcinoma (PTC) from 1987 to 2016 at Liverpool Hospital, this retrospective study investigated the association between microscopic positive margins in PTC and disease recurrence, and concluded that microscopic positive margins in PTC do not impact disease recurrence. Herein, we would like to raise the following comments.…”
mentioning
confidence: 99%
“…Therefore, comprehensive consideration could be taken according to individual differences and tumor characteristics to ensure the integrity of tumor resection and individualized treatment. 30 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies on microscopic positive tumour margins have reported that there is no association with recurrence. [14][15][16] Recently, Abraham et al 17,18 reported that microscopic positive tumour margins did not affect disease-free survival in the majority of patients with PTC, but was associated with a four-fold increased risk of recurrence in T4a patients. This supports the results of our study, which was conducted among T4a patients with RLN involvement.…”
Section: Discussionmentioning
confidence: 99%